2018
DOI: 10.3389/fmicb.2018.02918
|View full text |Cite
|
Sign up to set email alerts
|

Novel Widespread Marine Oomycetes Parasitising Diatoms, Including the Toxic Genus Pseudo-nitzschia: Genetic, Morphological, and Ecological Characterisation

Abstract: Parasites are key drivers of phytoplankton bloom dynamics and related aquatic ecosystem processes. Yet, the dearth of morphological and molecular information hinders the assessment of their diversity and ecological role. Using single-cell techniques, we characterise morphologically and molecularly, intracellular parasitoids infecting four potentially toxin-producing Pseudo-nitzschia and one Melosira species on the North Atlantic coast. These sequences define two, morphologically indistinguishable clades within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 76 publications
2
50
2
Order By: Relevance
“…in D. perforans subsp, destruens in Coscinodiscus), additional wall thickening will not take place, as evidenced by the very slight thickening of D. perforans isolates on C. concinnus, while the same isolates would form it on P. intermedium. Therefore, this feature seems not to be constant, which is why a differentiation based on it (Garvetto et al (2018) is probably not reliable. Sparrow (1936) reported that D. perforans zoospores are anteriorly biflagellate and oppositely directed, which is similar to what has been documented in all of the isolates of the current study, and different from previous observations (Petersen 1905(Petersen , 1909Höhnk 1939;Aleem 1953).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…in D. perforans subsp, destruens in Coscinodiscus), additional wall thickening will not take place, as evidenced by the very slight thickening of D. perforans isolates on C. concinnus, while the same isolates would form it on P. intermedium. Therefore, this feature seems not to be constant, which is why a differentiation based on it (Garvetto et al (2018) is probably not reliable. Sparrow (1936) reported that D. perforans zoospores are anteriorly biflagellate and oppositely directed, which is similar to what has been documented in all of the isolates of the current study, and different from previous observations (Petersen 1905(Petersen , 1909Höhnk 1939;Aleem 1953).…”
Section: Discussionmentioning
confidence: 99%
“…Positive clones were sent for sequencing to the laboratory centre of the Senckenberg Biodiversity and Climate Research Centre (Frankfurt am Main, Germany) using M13 (M13-F, M13-R), T3, and T7 plasmid primers. The resulting sequences were prepared using Geneious (version 5.6), and the assembled sequences of the oomycetes infecting L. abbreviata, S. ulna, C. concinnus and P. intermedium were added to the dataset of Buaya and Thines (2020), to which also additional sequences from Garvetto et al 2018Garvetto et al , 2020 were added, aligned using muscle (Edgar 2004) as implemented in MEGA5 (Tamura et al 2011), with a gap opening penalty of 600 and a gap extension penalty of 6. Phylogenetic analyses were done using MEGA5 for Minimum Evolution analysis with 1000 bootstrap replicates, and on the TrEase webserver (http://thineslab.senckenberg.de/trease/), using RAxML (Stamatakis 2014) for Maximum Likelihood inference, also with 1000 bootstrap replicates.…”
Section: Dna Extraction Pcr Amplification and Phylogenetic Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most likely, these sequences were amplified from fungal spores which would indicate that gutters could act as a vector. A number of known plant and algae (including diatoms) parasites belong to the Oomycetes clade (Kuhn and Hofmann, 1999;Scholz et al, 2016;Garvette et al, 2018;Leonard et al, 2018). Among the Oomycetes, 14 OTUs assigned to the Phytophthora genus were identified in 18 samples.…”
Section: Discussionmentioning
confidence: 99%